0682 Evaluation Of An Incentive-based Intervention To Improve 90-day Adherence In Pap-naive Patients. (27th May 2020) - Merchant, G; Valentine, K; Hevener, W; Willes, L; Ta, D; Hernandez, R; Gagnon, R; Chen, K; Blase, A
Abstract: Introduction: Although PAP therapy is the gold standard treatment for obstructive sleep apnea, adherence to treatment is suboptimal. Without sustained therapy adherence, patients are at risk of serious negative health outcomes. The objective of this study was to test whether a digitally delivered monetary and social reward program helped patients new to PAP therapy. Financial incentive schemes are effective in helping patients adhere to difficult medication or therapy plans. Additionally, there is an abundance of evidence that social support is a critical component to long-term health behavior change. Methods: This prospective, randomized, single site pilot is evaluating the effectiveness of an app-based intervention in helping patients adhere to PAP therapy. The financial incentive design leverages loss aversion, and the social incentive design leverages the strength of close ties and variable reinforcement. The primary endpoint is mean PAP usage at 3 months. Secondary endpoints include Medicare compliance, change in functional status, and baseline scores of perceived disease severity, claustrophobia, coping skills, and health literacy as moderators of the intervention's effectiveness. Study recruitment is ongoing, with an expected sample size of 150 subjects. Results: Of the 132 subjects enrolled, 56% are male, 61% are Caucasian, and 65% are married. The mean age is 49.6 ± 12.0 years and mean BMI is 32.4 ± 8.4 kg/m 2 . Additional demographics such as income level, education level, and number of children along with the primary and secondary endpoints will be presented. A subgroup analysis of the primary endpoint will be generated for subjects identified as strugglers within the first 3 days of usage. Conclusion: The results of this study will provide insight into methods such as financial and social incentives delivered via a smartphone on initial compliance with PAP therapy, as well as provide more information on the behavioral change associated with beginning PAP therapy. Support: ResMed